Avoiding Getting Lost in Song Translation: The Annotated Study - Yeni Artanti; Azhari Azhari; Muhammad Zikrullah; Dinda Destari (Center of Language Development, Institut Agama Islam Negeri Madura, 2025)
The rapid advancement of digital technology has led many texts to be freely translated by anyone or anything, including machine translation, without paying attention to the context or linguistic rules, resulting in misleadingly translated texts. Technological advances that allow everyone to have free access to anything have made it easy for anyone to obtain texts. The study used annotated translations to correct the misleading renderings of Putri Ariani’s songs,